2002
DOI: 10.1097/00000542-200204000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reverses Deficits of Cognitive Function and Memory and Increased Heart Rate Induced by Acute Severe Isovolemic Anemia

Abstract: The authors confirmed that acute isovolemic anemia subtly slows human reaction time, degrades memory, increases heart rate, and decreases energy level. The findings of this study support the hypothesis that increasing Pao2 to 350 mmHg or greater by breathing oxygen reverses all of these effects of acute anemia except for decreased energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
1
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(107 citation statements)
references
References 4 publications
1
95
1
10
Order By: Relevance
“…These data suggest that limited oxygen delivery impacted neurological function at Hb values near 50-60 gÁL -1 . 63 Fig. 2 Schematic representation of arterial, microvascular, and tissue oxygen gradients in control, anemic, and anemic b-blocked rats derived from previously published experimental data.…”
Section: Hemodilution Results In Reduced Microvascular Tissue Pomentioning
confidence: 99%
“…These data suggest that limited oxygen delivery impacted neurological function at Hb values near 50-60 gÁL -1 . 63 Fig. 2 Schematic representation of arterial, microvascular, and tissue oxygen gradients in control, anemic, and anemic b-blocked rats derived from previously published experimental data.…”
Section: Hemodilution Results In Reduced Microvascular Tissue Pomentioning
confidence: 99%
“…It is appealing to correlate the Ht level to quality of life and energy scores as it has already been demonstrated in renal insufficiency and after chemotherapy. [21][22][23][24][25] Furthermore, Ht on the day following surgery and on the day of discharge were significantly higher in the EPO than in the ABD group. Assessment of early postoperative recovery, (vigour and functional ability) in surgical patients is considered to be important for optimizing patient rehabilitation, discharge planning and health system resource utilization.…”
mentioning
confidence: 86%
“…Cognitive function and memory are usually affected at 6 g per 100 ml but can be partially corrected with supplemental oxygen. 45,46 Electrocardiographic changes occurred in only 5% of normal volunteers at Hb of 5 g per 100 ml. 47 A 1988 case-control study of surgical patients refusing blood transfusion found a 61.5% mortality with preoperative Hb o6.0 g per 100 ml.…”
Section: Rbc Transfusion In Stem Cell Transplantationmentioning
confidence: 99%